Making Of Flash Card And Augmented Reality-Based Application As A Learning Media For Children With Special Needs - Robby Kurniawan Budhi (Jurusan Teknologi Informasi Universitas Semarang, 2019)
This study aims to measure the level of effectiveness of the use of flash cards and applications based on Augmented Reality as a learning aid. The use of Android applications and AR cards that can also function as flash cards has proven to attract interest and increase student motivation in learning. Number recognition material and addition of unit numbers are chosen as the initial experiment stage which aims to introduce the use of assistive devices in the form of tablet PCs or smartphones to the children. Based on the results of the study, both teachers and students felt helped by the existence of this application as a variety of learning media. The research method used in this study is Multiple Baseline Design Across Subjects, while the sampling technique used is census sampling technique.